The outcomes of humanistic nursing for critical care nurses: A qualitative study - Zeynab Zamaniniya; Mojgan Khademi; Tahereh Toulabi; Kourosh Zarea (Nursing and Midwifery Studies, 2021)
Background: Despite the importance and the necessity of humanistic approaches to care, there are limited studies into their outcomes for nurses. Objectives: The aim of this study was to explore the outcomes of humanistic nursing for critical care nurses (CCNs). Methods: This qualitative study was conducted through conventional content analysis. Data were collected through semi-structured interviews with 16 CCNs purposively selected from hospitals in Ahvaz, Iran. Trustworthiness of the data was ensured using Lincoln and Guba's criteria. Results: The outcomes of humanistic nursing were grouped into three main categories, namely personal growth and self-actualization, protection of personal dignity, and greater satisfaction and comfort. Each of these categories had three subcategories which were development of abilities, self-concept and self-worth, spiritual transcendence; greater popularity, improved social status of nursing, appreciation, respect, and support for nurses; and happiness, satisfaction, and motivation, respectively. Conclusion: Humanistic approaches to care help fulfill the needs of both patients and nurses. The findings of this study provide a deeper understanding about how to reinforce humanistic behaviors and can be used in nursing education and practice.